Measurements and analysis of cavitation in a pressure reducing valve during operation a case study - Ulanicki,B; Picinali,L; Janus,T (Elsevier, 2015)
This paper proposes a methodology and presents its practical application for evaluating whether a pressure reducing valve (PRV) is under cavitation during its operation in a water distribution system. The approach is based on collecting measurements over a 24-hour period such that high demand and low demand times are included. The collected measurements allow evaluation of four indicators related to cavitation, namely the hydraulic cavitation index, noise generated by the valve, acoustic cavitation index and the spectra of the noise. These four indicators provide sufficient information for diagnosis of cavitation with high certainty.